The characteristics of intestinal microbiota in patients with chronic schistosomiasis japonica-induced liver fibrosis by 16S rRNA gene sequence - Guo, Chen; Zhang, Pengpeng; Li, Junhui; Zhou, Chen; Yang, Zhen; Zhang, Yu; Luo, Yulin; Zhou, Jie; Cai, Yu; Ming, Yingzi (Frontiers in Microbiology, 2023)
Background: The intestinal microbiota is known to play a role in the development of liver disease, there is a limited understanding of the intestinal microbiota associated with chronic schistosomiasis japonica. This study sought to explore the characteristics of the intestinal microbiota in patients with chronic schistosomiasis japonica and identify potential biomarkers that could aid diagnosis. Methods: A total of 40 residents of Qingshan Island in Yueyang (Hunan, China) were enrolled in this cross-sectional study. These individuals were divided into two groups for analysis of the intestinal microbiota: patients with chronic schistosomiasis japonica -induced liver fibrosis group (CSJ group, n=10) and a healthy control group (HC group, n=30). Feces were collected from each participant and analyzed by 16S rRNA gene sequencing, which included species composition analysis at the phylum and family levels, α and β diversity analysis, LEfSe, Kyoto Encyclopedia of Genes and Genome (KEGG) and Clusters of Orthologous Groups of proteins (COG) analysis. Results: Our results indicated that Schistosoma japonicum infection changed the composition and abundance of intestinal microbiota at the phylum and family levels. Compared with the HC group, the α and β diversity results showed that CSJ group had low diversity of species of the intestinal microbiome. LEfSe and relative abundance analysis found that the Prevotella 7, Alloprevotella and Holdemanella genera were significantly higher in the CSJ group than in the HC group. Meanwhile, the ROC analysis showed that the area under the curve (AUC) of Prevotella 7, Alloprevotella and Holdemanella genera was 0.779, 0.769 and 0.840 respectively. KEGG and COG analysis showed that the Replication and Repair and Defense Mechanism pathways correlated strongly with chronic schistosomiasis japonica infection. Conclusions: The current study was the first to explore differences in the intestinal microbiota of patients with chronic schistosomiasis japonica -induced liver fibrosis and healthy people from Qingshan Island, which indicated that Prevotella 7, Alloprevotella and Holdemanella genera could have a potential value in noninvasive diagnosis of chronic schistosomiasis japonica-induced fibrosis.